Quantifying amorphous and crystalline phase content with the atomic pair distribution function. (18th March 2013) - Peterson, Joseph; TenCate, James; Proffen, Thomas; Darling, Timothy; Nakotte, Heinz; Page, Katharine
<x xml:space="preserve">Abstract</x> Pair distribution function (PDF) analysis is a long‐established technique for studying the local structure of amorphous and disordered crystalline materials. In today's increasingly complex materials landscape, the coexistence of amorphous and crystalline phases within single samples is not uncommon. Though a couple of reports have been published studying samples with amorphous and crystalline phases utilizing PDF analysis, to date little has been done to determine the sensitivity that the method currently has in resolving such contributions. This article reports a series of experiments that have been conducted on samples with known ratios of crystalline quartz and amorphous glassy silica to examine this question in detail. Systematic methods are proposed to obtain the best possible resolution in samples with unknown phase ratios and some problems that one might encounter during analysis are discussed.